SYNERGY BETWEEN PUBLIC AND PRIVATE LAW IN REALISING A HEALTHY BUSINESS CLIMATE: A STUDY ON THE IMPLEMENTATION OF THE PRINCIPLE OF BALANCE IN NATIONAL ECONOMIC LAW - Gunawan Widjaja; Dyah Ersita Yustanti; Rio Johan Putra (CV. Adiba Aisha Amira, 2025)
This study discusses the synergy between public and private law in creating a healthy business climate in Indonesia, with a focus on the implementation of the principle of balance in national economic law. The synergy between these two areas of law is key to creating an economic system that is fair, efficient, and responsive to the dynamics of the modern economy. The study employs a normative legal method with a legislative approach and literature review, analysing written legal norms as well as relevant doctrines and court rulings. The results of the study indicate that the implementation of the principle of balance is crucial for maintaining the proportion of rights and obligations of parties in economic legal relationships, whether in business agreements, commercial transactions, or macro-level regulations. However, its implementation still faces various challenges, such as unequal bargaining positions, low legal literacy, regulations that are not adaptive, and weak law enforcement. Proposed solutions include strengthening legal literacy, regulatory reform, enhanced oversight, and collaboration between the government, businesses, and the public. Thus, the synergy between public and private law and the implementation of the principle of balance are expected to create a healthy, fair, and sustainable business ecosystem in Indonesia.